Effects of hypoxia and ocean acidification on the upper thermal niche boundaries of coral reef fishes. (31st July 2017) - Ern, Rasmus; Johansen, Jacob L.; Rummer, Jodie L.; Esbaugh, Andrew J.
Abstract : Rising ocean temperatures are predicted to cause a poleward shift in the distribution of marine fishes occupying the extent of latitudes tolerable within their thermal range boundaries. A prevailing theory suggests that the upper thermal limits of fishes are constrained by hypoxia and ocean acidification. However, some eurythermal fish species do not conform to this theory, and maintain their upper thermal limits in hypoxia. Here we determine if the same is true for stenothermal species. In three coral reef fish species we tested the effect of hypoxia on upper thermal limits, measured as critical thermal maximum (CTmax ). In one of these species we also quantified the effect of hypoxia on oxygen supply capacity, measured as aerobic scope (AS). In this species we also tested the effect of elevated CO2 (simulated ocean acidification) on the hypoxia sensitivity of CTmax . We found that CTmax was unaffected by progressive hypoxia down to approximately 35 mmHg, despite a substantial hypoxia-induced reduction in AS. Below approximately 35 mmHg, CTmax declined sharply with water oxygen tension ( P w O2 ). Furthermore, the hypoxia sensitivity of CTmax was unaffected by elevated CO2 . Our findings show that moderate hypoxia and ocean acidification do not constrain the upper thermal limits of these tropical, stenothermal fishes.